Diarrhoea and Suboptimal Feeding Practices in Nigeria: Evidence from the National Household Surveys. Issue 4 (24th March 2016) - Ogbo, Felix A.; Page, Andrew; Idoko, John; Claudio, Fernanda; Agho, Kingsley E.
Abstract: Background: Globally, Nigeria has the largest burden of infectious diseases (including diarrhoea). Optimal feeding practices have been well‐documented to protect against diarrhoea in other contexts; but this benefit has not been broadly studied in Nigeria. The study aimed to examine the association between diarrhoea and childhood feeding practices to provide country‐specific evidence. Method: Data from the Nigeria Demographic and Health Survey for the period spanning 1999–2013 were used. Prevalence of diarrhoea by infant and young child feeding indicators was estimated, and the association between diarrhoea and childhood feeding indicators was examined using multilevel regression analyses. Results: Prevalence of diarrhoea was higher among children whose mothers did not initiate breast feeding within the first hour of birth, infants who were not exclusively breastfed, and infants who were prematurely introduced to complementary foods. Early initiation of breast feeding was significantly associated with lower risk of diarrhoea (RR 0.68, 95% confidence interval (CI) 0.63, 0.74). Exclusively breastfed infants were less likely to develop diarrhoea compared to non‐exclusively breastfed infants (RR 0.61, 95% CI 0.44, 0.86). Predominant breast feeding was significantly associated with a lower risk of diarrhoea (RR 0.66, 95% CI 0.54, 0.80). Bottle feeding and introduction of complementary foods were associated with a higher risk of diarrhoea. Conclusion: Early initiation of breast feeding as well as exclusive and predominant breast feeding protect against diarrhoea in Nigeria, while bottle feeding and introduction of complementary foods were risk factors for diarrhoea. Community‐ and facility‐based initiatives are needed to improve feeding practices, and to reduce diarrhoea prevalence in Nigeria.